Experimental Evaluation of the Optimal Suture Pattern With a Flexible Endoscopic Suturing System. (June 2017) - Halvax, Peter; Diana, Michele; Nagao, Yoshihiro; Marescaux, Jacques; Swanström, Lee
Background . The ability to perform reliable, secure endoluminal closure of the gastrointestinal tract wall, is a prerequisite to support the progress of the emerging field of endoluminal surgery. Along with advanced clipping systems, flexible endoscopic suturing devices are commercially available. Current systems can replicate traditional surgical suturing patterns in the endoluminal environment. The aim of this study was to evaluate the optimal endoluminal suturing technique using a flexible endoscopic suturing device. Materials and Methods . Procedures were performed on bench-top simulators containing 20 explanted porcine stomachs. A standardized 3-cm full-thickness incision was created on the anterior wall of each stomach using monopolar cautery. The gastrotomy was closed endoscopically using an over-the-scope suturing device (OverStitch, Apollo Endosurgery; Austin, TX). Three different techniques were used: single stitches, figure-of-8 pattern, and running suture. Material consumption and operation time were recorded and bursting pressure measurement of the closure was performed. Results . No statistically significant differences were identified in suturing time. Suturing time (minutes) was slightly shorter with the figure-of-8 technique (41.14 ± 4.6) versus interrupted (45.75 ± 1.1) versus continuous (51.44 ± 10.0), but the difference was not statistically significant. The number of sutures required was greater in the interrupted group. No significant difference was found in the burst pressure (mm Hg): figure-of-8 (45.85 ± 26.2) versus interrupted (30.5 ± 22.89) versus continuous (32.0 ± 26.5). In the figure-of-8 group, 85.5% of cases were leakproof above 30 mm Hg, while in the other groups only 50% of cases were so. Conclusion . A figure-of-8 suturing pattern seems to be the preferable suturing technique with the endoscopic suturing device.